Risk factors for silent and symptomatic atrial fibrillation in an elderly population screening programme:a report from the noninvasive monitoring for early detection of atrial fibrillation (NOMED-AF). (25th November 2020) - Mitrega, K; Sredniawa, B; Stokwiszewski, J; Sokal, A; Boidol, J; Wierucki, L; Bleszynska, E; Bandosz, P; Rutkowski, M; Zdrojewski, T; Kazmierczak, J; Opolski, G; et al.
Abstract: Background: It is important to determine the risk factors that predispose elderly subjects from the general population for symptomatic atrial fibrillation and atrial flutter (AF/AFl), but population-based data for silent AF (SAF) are limited. Aim: To study risk factors for symptomatic AF and SAF in a general population screen for subjects age ≥65 where continuous monitoring was performed up to 30 days with a vest-based monitor. Methods: The NOMED-AF study was a cross-sectional study based on a representative population sample (n=3014; mean age 77.5±7.9 years; F=1479). In 680 subjects AF/AFl (including 279 with SAF) was diagnosed. Independent risk factors for AF/AFl and SAF were determine on weighted data using multiple logistic regression. Results: The independent risk factors for AF/AFl and SAF are summarised in the Table. There are nine independent risk factors for AF/AFl and eight for SAF. Revascularization and obesity were independently associated with patients with (symptomatic) AF/AFl, and CKD was associated with SAF. Other risk factors are common for AF/AFl and SAF. Conclusions: AF/AFl and SAF have slightly different associated clinical risk factors in this representative population sample aged ≥65 years. This may facilitated targeted screening programmes for high risk subgroups, particularly for SAF. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): The research has received funding from the National Centre for Research and Development under grant agreement (STRATEGMED2/269343/18/NCBR/2016)